Influence of Multiple Cardiovascular Risk Factors on Task-Switching in Older Adults: An fMRI Study - Qin, Shuo; Basak, Chandramallika (Frontiers in Human Neuroscience, 2020)
Not only are the effects of cardiovascular risk factors such as high blood pressure and low fitness on executive functions and brain activations in older adults scarcely investigated, no fMRI study has investigated the combined effects of multiple risk factors on brain activations in older adults. This fMRI study examined the independent and combined effects of two cardiovascular risk factors, arterial plasticity and physical fitness, on brain activations during task-switching in older adults. The effects of these two risk factors on age-related differences in activation between older and younger adults were also examined. Independently, low physical fitness and low arterial plasticity were related to reduced suppressions of occipital brain regions. Combined effects of these two risks on occipital regions were greater than the independent effects of either risk factor. Age-related overactivations in frontal cortex were observed in low fitness older adults. Brain-behavior correlation indicates that these frontal overactivations are maladaptive to older adults’ task performance. It is possible that effects of cardiovascular risks on posterior brain regions disengagement as well as on maladaptive overactivations of frontal brain regions contribute to the anterior-posterior shift in aging (PASA). Furthermore, observed age-related differences in brain activations during task-switching could be partially attributed to individual differences in cardiovascular risks among older adults.